Design, Synthesis and Antimicrobial Evaluation of New N-(1-Hydroxy-1,3-dihydrobenzo[c][1,2]oxaborol-6-yl)(hetero)aryl-2-carboxamides as Potential Inhibitors of Mycobacterial Leucyl-tRNA Synthetase - Šlechta, Petr; Needle, Adam Anthony; Jand'ourek, Ondřej; Paterová, Pavla; Konečná, Klára; Bárta, Pavel; Kuneš, Jiří; Kubíček, Vladimír; Doležal, Martin; Kučerová-Chlupáčová, Marta (International journal of molecular sciences, 2023)
Tuberculosis remains a serious killer among infectious diseases due to its incidence, mortality, and occurrence of resistant mycobacterial strains. The challenge to discover new antimycobacterial agents forced us to prepare a series of N-(1-hydroxy-1,3-dihydrobenzo[c][1,2]oxaborol-6-yl)(hetero)aryl-2-carboxamides 1-19 via the acylation of 6-aminobenzo[c][1,2]oxaborol-1(3H)-ol with various activated (hetero)arylcarboxylic acids. These novel compounds have been tested in vitro against a panel of clinically important fungi and bacteria, including mycobacteria. Some of the compounds inhibited the growth of mycobacteria in the range of micromolar concentrations and retained this activity also against multidrug-resistant clinical isolates. Half the maximal inhibitory concentrations against the HepG2 cell line indicated an acceptable toxicological profile. No growth inhibition of other bacteria and fungi demonstrated selectivity of the compounds against mycobacteria. The structure-activity relationships have been derived and supported with a molecular docking study, which confirmed a selectivity toward the potential target leucyl-tRNA synthetase without an impact on the human enzyme. The presented compounds can become important materials in antimycobacterial research.
Keywords: Microbial Sensitivity Tests; Humans; Fungi; antituberkulotika; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; houby; Molecular Docking Simulation; mikrobiální testy citlivosti; Anti-Infective Agents; aminoacyl-tRNA-synthetasy; antiinfekční látky; Amides; lidé; antibakteriální látky; Anti-Bacterial Agents; Antitubercular Agents; Mycobacterium tuberculosis; Amino Acyl-tRNA Synthetases; amidy